2007
DOI: 10.1111/j.1365-2621.2007.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Food applications of trans fatty acid substitutes

Abstract: The review outlines the increasing need to reduce trans fatty acids, and addresses the functionality issues of various trans free solutions through discussion of hydrogenation, interesterification, and fractionation, and their influence on fat crystallisation and solid fat content. Caution is urged not to focus solely on physiochemical aspects, but to approach trans free designing for specific food applications from a multidisciplinary angle. Examples of specific applications; margarines, shortenings and fryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 26 publications
3
128
0
10
Order By: Relevance
“…The binary blends of 70:30 w/w MoO/VCO can be regarded as offering good spreadability at low temperatures (10 °C) with SFC values of 23.1 to 11.2% after 0 to 24 h IE, respectively. The product's stability and its resistance to oiling-out could be characterized in fats with a minimum of 10% SFC between 20 and 22 °C (Lida et al, 1998;Wassell and Young, 2007). The unreacted binary blend of MoO/VCO 30:70 w/w with 20.1% and 10.9% SFC at 20 and 22 °C, respectively and the interesterified blend after 6 h with 11.3% SFC fall within this group of fats.…”
Section: Effect Of Enzymatic Interesterifi Cation On Solid Fat Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The binary blends of 70:30 w/w MoO/VCO can be regarded as offering good spreadability at low temperatures (10 °C) with SFC values of 23.1 to 11.2% after 0 to 24 h IE, respectively. The product's stability and its resistance to oiling-out could be characterized in fats with a minimum of 10% SFC between 20 and 22 °C (Lida et al, 1998;Wassell and Young, 2007). The unreacted binary blend of MoO/VCO 30:70 w/w with 20.1% and 10.9% SFC at 20 and 22 °C, respectively and the interesterified blend after 6 h with 11.3% SFC fall within this group of fats.…”
Section: Effect Of Enzymatic Interesterifi Cation On Solid Fat Contentmentioning
confidence: 99%
“…At low temperatures (4-10 °C), where SFC gives an indication of the fat's spreadability, VCO originally do not offer satisfactory characteristics with SFC values of 89.8%. Ribeiro et al (2009), Wassell andYoung (2007) and Lida and Ali (1998) demonstrated that for spreadability at refrigeration temperatures, the SFC should not exceed 32% at 10 °C in order to meet the minimum plasticity requirement. The binary blends of 70:30 w/w MoO/VCO can be regarded as offering good spreadability at low temperatures (10 °C) with SFC values of 23.1 to 11.2% after 0 to 24 h IE, respectively.…”
Section: Effect Of Enzymatic Interesterifi Cation On Solid Fat Contentmentioning
confidence: 99%
“…This information helps in the optimization of their usage in industrial processing, especially when the technology requires cooling steps [18]. Crystallization kinetics deeply influences the final structure of fats and is intrinsically related to their rheological and plasticity properties.…”
Section: Solidification Studymentioning
confidence: 99%
“…Increasing need to reduce trans fatty acids and functionality of various trans-free fats developed through various modification processes were discussed (Wassell and Young, 2007). The concern over TFA on health, has led development of trans-free speciality fats similar to vanaspati.…”
Section: Introductionmentioning
confidence: 99%